The Wiley-Blackwell handbook of judgment and decision making - Keren, Gideon; Wu, George (Chichester, West Sussex : Wiley-Blackwell, 2015)
'This two-volume reference is a comprehensive, up-to-date examination of the most important theory, concepts, methodological approaches, and applications in the burgeoning field of judgment and decision making (JDM). Brings together a multi-disciplinary group of contributors from across the social sciences, including psychology, economics, marketing, finance, public policy, sociology, and philosophy Provides accessible, essential information, complete with the latest research and references, for experts and non-experts alike in two volumes Emphasizes the growth of JDM applications with separate chapters devoted to medical decision making, decision making and the law, consumer behavior, and more Addresses controversial topics (such as choice from description vs. choice from experience and contrasts between empirical methodologies employed in behavioral economics and psychology) from multiple perspectives'--
'A comprehensive, up-to-date examination of the most important theory, concepts, methodological approaches, and applications in the burgeoning field of judgment and decision making'--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Decision making; Judgment; PSYCHOLOGY -- Cognitive Psychology; Decision making; Judgment; Electronic books